Hypotrichosis with keratosis pilaris: a case report and review of literature - Ayman M Mahran; Aya Y Badran; Asmaa M Ahmad; Mahmoud R Hussein (Wolters Kluwer Medknow Publications, 2017)
Hypotrichosis or sparse hair is a relatively common feature of several hereditary syndromes. Hypotrichosis with keratosis pilaris is a very rare inborn skin disorder of unknown etiology. Here we report a rare case of hypotrichosis with keratosis pilaris in a 7-year-old boy. To the best of our knowledge, this is the first case to be reported from Egypt. The clinicopathological features were presented and the relevant literature was addressed.